STUDENTS' PERCEPTIONS OF INSTAGRAM-BASED ENGLISH LEARNING MATERIALS IN IMPROVING WRITING SKILLS: A QUALITATIVE STUDY - Meliana; Mariana Efrasia Dade; Baiti Nabila sari; Rampeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of social media in English language learning has transformed how students access learning materials and develop language skills. Among various platforms, Instagram has become popular because of its visual features, interactive content, and accessibility. It provides authentic English learning materials, including vocabulary, grammar explanations, captions, reels, and writing activities that support language development. However, limited research has examined students’ perceptions of Instagram-based learning materials, particularly regarding their contribution to writing skills. Therefore, this study investigates students’ perceptions of Instagram as a source of English learning materials and its role in improving writing skills. This study employed a qualitative approach involving twelve undergraduate students from the English Education Department who had regularly used Instagram-based English learning materials for at least one semester. Data were collected through semi-structured interviews and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings revealed three major themes. Instagram provides engaging and authentic learning materials that motivate students to practice writing. Its visual and multimedia features improve vocabulary, grammar, and writing organization. Although students generally perceive Instagram positively, they also experience challenges such as distractions, inconsistent content quality, and limited teacher guidance. The study concludes that Instagram-based English learning materials enhance students’ motivation, confidence, autonomous learning, and writing skills. These findings suggest that English teachers should integrate carefully selected Instagram content into writing instruction to promote meaningful learning and strengthen students’ digital literacy.